Strengthening family–school partnerships through research, training and innovation: Reflections from the MTA‑DE‑PARTNERED program - Kocsis, Zsófia; G. Hine, Megumi; Ceglédi, Tímea; Bacskai, Katinka (Central European Journal of Educational Research, 2026)
This study presents the comprehensive findings of the MTA-DE-PARTNERED research and development program, which ran from 2021 to 2025, and aimed to explore and develop the theoretical, empirical, and practical dimensions of family-school partnerships. Within the framework of Epstein’s model of parental involvement, the research examined parents’ educational and learning-support activities at home, school–parent communication, volunteering, participation in decision-making, and community building. Analyses based on a review of the literature, large-scale questionnaire surveys, interviews, and case studies show that patterns of parental involvement are influenced by the child’s achievement, school type, school sector, and social background. The MTA-DE-PARTNERED program placed a strong emphasis on improving teacher training, recognizing that teachers’ preparedness and attitudes play a key role in the quality of the partnership. During the development phase, we created an evidence-based collection of best practices, a university toolkit, and an innovative educational board game based on cooperative. The board game aimed to support the positive development of asset-based attitudes among students and teachers through the simulation of various parental involvement scenarios. The results of the impact assessments suggest that the board game significantly contributes to the development of reflective thinking, a multi-perspective approach, and partnership-centered attitudes. This study shows that strengthening family-school collaboration requires systemic, research-based, and training-related innovations that will, in the long term, contribute to the improvement of student achievement and the development of pedagogical culture.